Democracy fatigue a East European epidemy - García-Rivero, Carlos (Central European University Press, 2023)
Cover -- Front matter -- Title page -- Copyright page -- Contents -- List of Figures -- List of Tables -- Introduction: European Democracy at the Crossroads -- Part 1 Populism in Europe: Concept and Context -- Chapter 1 Quality of Democracy in Europe -- Chapter 2 Populism: Theoretical Foundations -- Chapter 3 Mapping European Populism and Its Association with Anti-Pluralism: Descriptive Evidence in Time and Space -- Chapter 4 On the Persistence of Radical Right Populism in Europe: The Role of Grievances and Emotions -- Part II Political Participation under Populism: Trends and Limits -- Chapter 5 The Limits of Democratic Competition: Time-Series, Cross-Sectional Evidence of the Asymmetrical Impact of Polarization on Europeans' Political Attitudes and Behavior -- Chapter 6 Populist Voter Profiles in Different Electoral Calls: Lessons from Spain -- Chapter 7 Ideological Congruence between Populist Right Parliamentary Elites and Their Voters: An Analysis of Poland, Sweden, and Germany -- Chapter 8 Internal Sanctions for Rule of Law Breaches under Article 7 TEU: Why Is the EU Dragging Its Feet? -- Part III Populist Parties in Different European Regions -- Chapter 9 Populism in Western versus Eastern Europe -- Chapter 10 Populism in Southern Europe -- Chapter 11 Nordic Populism: Conjoining Ethno-Nationalism and Welfare Chauvinism -- Conclusion: What Lies Ahead -- About the Contributors -- Index -- Back cover.